Initial Viral Inoculum Determines Kinapse-and Synapse-Like T Cell Motility in Reactive Lymph Nodes - Sivapatham, Sujana; Ficht, Xenia; Barreto de Albuquerque, Juliana; Page, Nicolas; Merkler, Doron; Stein, Jens V. (Frontiers in Immunology, 2019)
T cell activation in lymphoid tissue occurs through interactions with cognate peptide-major histocompability complex (pMHC)-presenting dendritic cells (DCs). Intravital imaging studies using ex vivo peptide-pulsed DCs have uncovered that cognate pMHC levels imprint a wide range of dynamic contacts between these two cell types. T cell - DC interactions vary between transient, “kinapse-like” contacts at low to moderate pMHC levels to immediate “synapse-like” arrest at DCs displaying high pMHC levels. To date, it remains unclear whether this pattern is recapitulated when the immune system faces a replicative agent, such as a virus, at low and high inoculum. Here, we locally administered low and high inoculum of lymphocytic choriomeningitis virus (LCMV) in mice to follow activation parameters of Ag-specific CD4+ and CD8+ T cells in draining lymph nodes (LNs) during the first 72 h post infection. We correlated these data with kinapse- and synapse-like motility patterns of Ag-specific T cells obtained by intravital imaging of draining LNs. Our data show that initial viral inoculum controls immediate synapse-like T cell arrest versus continuous kinapse-like motility. This remains the case when the viral inoculum and thus the inflammatory microenvironment in draining LNs remains identical but cognate pMHC levels vary. Our data imply that the Ag-processing capacity of draining LNs is equipped to rapidly present high levels of cognate pMHC when antigenic material is abundant. Our findings further suggest that widespread T cell arrest during the first 72 h of an antimicrobial immune responses is not required to trigger proliferation. In sum, T cells adapt their scanning behavior according to available antigen levels during viral infections, with dynamic changes in motility occurring before detectable expression of early activation markers.